2017
DOI: 10.1002/2017tc004525
|View full text |Cite
|
Sign up to set email alerts
|

Zircon, titanite, and apatite (U‐Th)/He ages and age‐eU correlations from the Fennoscandian Shield, southern Sweden

Abstract: Craton cores far from plate boundaries have traditionally been viewed as stable features that experience minimal vertical motion over 100–1000 Ma time scales. Here we show that the Fennoscandian Shield in southeastern Sweden experienced several episodes of burial and exhumation from ~1800 Ma to the present. Apatite, titanite, and zircon (U‐Th)/He ages from surface samples and drill cores constrain the long‐term, low‐temperature history of the Laxemar region. Single grain titanite and zircon (U‐Th)/He ages are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 75 publications
(133 reference statements)
4
51
0
Order By: Relevance
“…Similar age variability to that in our ZHe data set is reported in other data sets from the Pyrenees and from other similar orogenic settings (e.g., Guenthner et al, , , ; Vacherat et al, , ). It has been demonstrated that this results from the inability of a single set of kinematic parameters for He diffusion to describe the natural thermochronometric behavior of zircon (Cherniak et al, ; Guenthner et al, ; Ketcham et al, ; Reiners et al, , ).…”
Section: (U‐th)/he Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Similar age variability to that in our ZHe data set is reported in other data sets from the Pyrenees and from other similar orogenic settings (e.g., Guenthner et al, , , ; Vacherat et al, , ). It has been demonstrated that this results from the inability of a single set of kinematic parameters for He diffusion to describe the natural thermochronometric behavior of zircon (Cherniak et al, ; Guenthner et al, ; Ketcham et al, ; Reiners et al, , ).…”
Section: (U‐th)/he Resultssupporting
confidence: 90%
“…These observations suggest that heterogeneous distribution of U and Th in our zircons, albeit likely contributing to some of the observed age irreproducibility in each sample, cannot alone explain the large spread in our ZHe ages. The remainder of this results section, and more generally this study, will therefore be mainly focused on the third main source of age variation in our ZHe data set: radiation damage (Guenthner et al, , 2014(Guenthner et al, , 2015(Guenthner et al, , 2017.…”
Section: (U-th)/he Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mean (U–Th)/He dates are commonly overdispersed, with standard deviations of the means exceeding analytical precision. Overdispersion is due to various factors that control He diffusivity and thus influence T c and dates, including diffusion‐domain length scale and cooling rate (Dodson, ; Farley, ; Jensen et al, ; Reiners & Farley, ), radiation damage accumulation (Baughman et al, ; Flowers et al, ; Gautheron et al, ; Guenthner et al, , ; Shuster & Farley, ), grain chemistry (Gautheron, Barbarand, et al, ), and grain breakage (Brown et al, ). Additional variables that cause He data dispersion include implantation of parentless He by adjacent U–Th‐rich phases (Gautheron et al, ; Murray et al, ; Spiegel et al, ), parent isotope zonation (Ault & Flowers, ; Farley et al, ; Gautheron, Barbarand, et al, ; Guenthner et al, ; Hourigan et al, ; Meesters & Dunai, ; Orme et al, ), microvoids or crystal defects (McDannell, Zeitler, Janes, et al, ; Zeitler et al, ), and inaccuracies in the alpha ejection correction factor owing to grain geometry or zoning (Farley et al, , ; Glotzbach et al, ).…”
Section: Analytical Uncertainties Models and Interpretationsmentioning
confidence: 99%
“…High eU zircon He dates can be younger than apatite He dates reflecting low T c . Titanite He dates similarly yield an inverse date‐eU relationship and older dates owing to lower eU values and higher T c (Baughman et al, ; Guenthner et al, ).…”
Section: Advances In Thermochronometry Systematicsmentioning
confidence: 99%